Hydrodynamics, residence time distribution, and mass transfer in spiral coils in series - Khan, Muzammilanwar S.; Deore, Hital S.; Kulkarni, Amol A. (Industrial and Engineering Chemistry Research, 2023)
Here, we report the analysis of flow field, residence time distribution (RTD), and mass transfer for the novel design of a spiral coil reactor (SCR) consisting of five spiral coils connected in series. Each coil comprises 8 turns with minimum and maximum radii of curvatures of 15 and 45 mm, respectively. The SCR is made up of an SS 316 tube (1/8 in. approximate to 3.175 mm O.D. and 1.8 mm I.D.), with a total length of 3.89 m. Experiments, as well as three-dimensional (3D) CFD simulations, are carried out to study the effects of the flow rate (61 <= Re-in <= 1839) on spatial variations in velocity and pressure distribution within the individual coils of the reactor. The flow regime is observed to undergo a transition from stable laminar flow for a lesser Dean number (De < 50) to dominant secondary flow vortices for De > 80. During the flow from the inner to the outer turns of the coil, the tangential velocity increases with a decreasing curvature ratio (delta), and the opposite occurs during the flow from the outer to the inner turns of the coil. Experimental RTD results show that the extent of axial dispersion decays exponentially with increasing Re and remains constant for Re > 500. For liquid-liquid two-phase flow, the spiral coils in series offer a mass transfer coefficient comparable to those of static mixers and agitated contactors but with significantly lesser power consumption per unit volume. This work gives new insights into the design of a spiral coil reactor suitable to carry out single-phase and multiphase reactions efficiently as possibly the most space-filling option of tubular reactors with excellent transport characteristics.
Keywords: Gas- Liquid; heat transfer coefficient; Liquid Taylor Flow

Scaling-up continuous production of mesoporous silica particles at kg scale: design & operational strategies - Jundale, Rajashri B.; Sonawane, Jayesh R.; Palghadmal, Anil V.; Jaiswal, Hemant Kumar; Deore, Hital S.; Kulkarni, Amol A. (Reaction Chemistry & Engineering, 2024)
This paper demonstrates a continuous flow pilot-scale production of highly porous mesoporous silica particles (MSPs) via a soft template based technique. The study presents pilot scale reactor design, fabrication and production of mesoporous silica particles with a 1 kg per day production rate. The extent of mixing and overall performance of the system were evaluated by conducting a hydrodynamic study, including the estimation of the heat transfer coefficient and dispersion number. Nanoparticle synthesis in a clogging-free manner is the key challenge in moving towards large scale production and commercial applications. This article presents a comprehensive study on the effect of key parameters for successful scaling up of the process. We have also addressed challenges faced and how these are overcome by troubleshooting the process. Different strategies were used to prevent the clogging of the reactor, which involved reactant dilution, periodic pulsation and slug flow (two phase flow). Among them, slug flow allows us to operate the reactor continuously for several hours without clogging and wall-deposition problems. It helped produce morphologically well-defined and near-monodisperse particles. With this process, the production is validated at a scale of 85 times compared to that of a laboratory system (from 22 mL to >1.5 L), enabling a production rate of 20-50 g h(-1).